PEMBERIAN KOLOSTRUM PERTAMA PADA BAYI BARU LAHIR DAN FAKTOR TERKAIT - Suci Rahmani Nurita (Universitas Baiturrahim, 2019)
Decreased use of breast milk 98% causes neonatal mortality in the world. One of the factors influencing the decrease is lactation management which is closely related to the practice of early breastfeeding in the form of colostrum. Delay in the giving of colostrum in early birth has an impact on the success of exclusive breastfeeding. This research is observational with cross sectional approach, aims to find out the probability of giving initial colostrum and related factors. The population in this study were 61 postpartum mothers and newborns in 2 hospitals (TK III Reksodiwiryo Hospital and DR. Rasyidin Hospital) and 4 Independent Midwives Practice (BPM) in the Andalas, Ambacang and Belimbing Community Health Centre. Samples were obtained by consecutive sampling. Statistical test results showed that in the vaginally group more than half of the respondents (42.9%) started giving colostrum <1 hour after birth while in the C-section born group most respondents (80.8%) started giving colostrum 7-23 hours after birth. Factors not related to when colostrum was first given to newborns were maternal education (p=0.654), occupation (p=1,000), parity (p=0.113) and infant sex (p=0.781). Factors related to when colostrum was first given to newborns were birth method (p=0,000) and infant birth weight (p=0.004). In this study it can be concluded that the probability of the first time colostrum was given by postpartum mothers was slower than that proclaimed by the ministry of health (30 minutes to 1 hour after birth) which was influenced by the way of birth of the baby and the birth weight of the baby. It is expected that the role of health workers in the Early Breastfeeding Initiation (IMD) as soon as possible after birth